Analysis of Factors Affecting the Quality of Public Services at Fauziah Bireuen Hospital - Diah, Muhammad; Firmansyah, Denny; haryani, Haryani; Safrina, Emi (Riwayat: Educational Journal of History and Humanities, 2025)
Quality public service Where the performance of public servants greatly influences the quality of patient services. Therefore, building a reliable public service management system is very necessary. This study aims to determine the factors that influence public services at Fauziah Hospital. The population in this study were patients who were undergoing treatment at Fauziah Hospital. The results of the study showed that tangibles and reliability influenced the quality of public services both partially and simultaneously.